2013
DOI: 10.1177/0333102413515344
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility to cortical spreading depression in an animal model of medication-overuse headache

Abstract: Objective The objective of this article is to evaluate electrically evoked thresholds for cortical spreading depression (CSD) and stress-induced activation of trigeminal afferents in a rat model of medication-overuse headache (MOH). Methods Sumatriptan or saline was delivered subcutaneously by osmotic minipump for six days to Sprague-Dawley rats. Two weeks after pump removal, animals were anesthetized and recording/stimulating electrodes implanted. The animals were pretreated with vehicle or topiramate follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
55
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 72 publications
9
55
0
1
Order By: Relevance
“…Medication-overuse headache is a major clinical problem (33), and has been observed with frequent use of SUMA (34). Administration of SUMA by minipump over multiple days has been shown previously to model medication-overuse headache (35,36). In this case chronic SUMA produced hyperalgesia in the head and peripheral regions concomitant with increased CGRP expression in trigeminal ganglia (35), and increased susceptibility to CSD (36).…”
Section: Discussionmentioning
confidence: 99%
“…Medication-overuse headache is a major clinical problem (33), and has been observed with frequent use of SUMA (34). Administration of SUMA by minipump over multiple days has been shown previously to model medication-overuse headache (35,36). In this case chronic SUMA produced hyperalgesia in the head and peripheral regions concomitant with increased CGRP expression in trigeminal ganglia (35), and increased susceptibility to CSD (36).…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to BLS was performed on days 20 and 21 post-sumatriptan treatment (46). Following the second BLS episode, periorbital and hindpaw withdrawal thresholds were tested at 1 h intervals over a 5 h time course.…”
Section: Methodsmentioning
confidence: 99%
“…One limitation in their clinical use is that they can contribute to migraine chronification and more frequent episodes of headache, a condition referred to as medication overuse headache (MOH), recently characterized as a global epidemic [9; 11; 27; 28; 38; 41; 45; 77]. The triptan receptors are both Gi-protein coupled, which they share with other classes of analgesics, including those that act at mu-opioid or CB cannabinoid receptors [67; 74].…”
Section: Discussionmentioning
confidence: 99%
“…Also, the frequent use of triptans can lead to transition to MOH or chronic migraine [9; 10; 27; 28; 38; 41; 68; 77; 85]. We observed that sumatriptan produces a neuroplastic change in nociceptor function such that PGE 2 -induced mechanical hyperalgesia is markedly prolonged, a characteristic feature of both type I [4; 29; 33; 50; 57; 69; 73] and type II [7; 8] hyperalgesic priming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation